JNK at the crossroad of obesity, insulin resistance, and cell stress response - Giovanni Solinas; Barbara Becattini (Elsevier, 2017)
Background: The cJun-N-terminal-kinase (JNK) plays a central role in the cell stress response, with outcomes ranging from cell death to cell proliferation and survival, depending on the specific context. JNK is also one of the most investigated signal transducers in obesity and insulin resistance, and studies have identified new molecular mechanisms linking obesity and insulin resistance. Emerging evidence indicates that whereas JNK1 and JNK2 isoforms promote the development of obesity and insulin resistance, JNK3 activity protects from excessive adiposity. Furthermore, current evidence indicates that JNK activity within specific cell types may, in specific stages of disease progression, promote cell tolerance to the stress associated with obesity and type-2 diabetes. Scope of review: This review provides an overview of the current literature on the role of JNK in the progression from obesity to insulin resistance, NAFLD, type-2 diabetes, and diabetes complications. Major conclusion: Whereas current evidence indicates that JNK1/2 inhibition may improve insulin sensitivity in obesity, the role of JNK in the progression from insulin resistance to diabetes, and its complications is largely unresolved. A better understanding of the role of JNK in the stress response to obesity and type-2 diabetes, and the development of isoform-specific inhibitors with specific tissue distribution will be necessary to exploit JNK as possible drug target for the treatment of type-2 diabetes. Keywords: Oxidative stress, Endoplasmic eeticulum stress, Autophagy, MAPK, Diabetes, Inflammation